The Comentarios Reales of the Inca Garcilaso de la Vega: its Argentine edition (1943-1944) - Colombi, Beatriz (Anales de Literatura Hispanoamericana, 2021)
This article analyzes Ángel Rosenblat’s edition of the Inca Garcilaso’s Comentarios Reales, published by Emecé (1944-45). It examines the problems of the editor function and postulates a balance between fidelity, modernization and mosaic, which results in a paradigmatic text for editions of the 20th century, not without revisions. In the first prologue, by Ricardo Rojas, the author articulates a founding story of the alliance between creoles and mestizos, highlights the political hierarchy of the text and consolidates its continental dimension, in dialogue with the previous and future criticism of the text.